Hom-Lie Triple System and Hom-Bol Algebra Structures on Hom-Maltsev and Right Hom-Alternative Algebras - ATTAN, SYLVAIN; ISSA, A. Nourou (My University, 2018)
Every multiplicative Hom-Maltsev algebra has a natural multiplicative Hom-Lie triple system structure. Moreover, there is a natural Hom-Bol algebra structure on every multiplicative Hom-Maltsev algebra and on every multiplicative right (or left) Hom-alternative algebra.
Keywords: Lie triple system; Malcev algebra; Hom-alternative algebra; Hom-Lie triple system; Hom-Malcev algebra; Hom-Bol algebra.